Legal Analysis of the Implementation of Restorative Justice in Dispute Resolution in Society - Tohawi, Agus; Myaskur, Myaskur; Ambodo, Triyo; Munir, Samsul; Salafiyah, Nurul (Borong Newinera Publisher, 2022)
This research aims to analyze the application of the Restorative Justice principle in dispute resolution within the community, using a juridical analysis approach. Restorative Justice is an alternative dispute resolution that prioritizes the restoration of relationships between the involved parties: victims, offenders, and society. The method used in this study is a normative method with a qualitative approach, examining relevant legal norms and their application in community dispute cases. The study also utilizes literature review to explore legal sources, literature, and journals related to the application of Restorative Justice in Indonesia. The objective of this research is to understand the effectiveness of Restorative Justice in resolving disputes, both legally and socially, and to identify the potential and challenges faced in its implementation. The research aims to provide recommendations for developing a legal system that is more focused on restoration and reconciliation.